Strategi Komunikasi Kampanye Produk Sosial Value dan Practices tentang Asi Eksklusif terhadap Target Market Pekerja - Indria Flowerina; Zike Marta (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
This research is conducted to describe the strategy communication of exclusive breast milk’s campaign by the Indonesian Lactation Center in socializing and enhancing the value and practices of exclusive breast feeding as a social product upon the target market: workers. As we know that actually exclusive breast milk can be given even though the mothers have to work and leave their babies as long as it is done by a good lactation management. This research will also talk about the view of working mothers upon the value and practices of breast feeding. Another objective of the research is to know what medias are affecting their attitude towards exclusive breast feeding. Research analysis was conducted by deep-interviewing the key informan, the head of Indonesian Lactation Center, towards the strategy of communication exclusive breast milk campaign by using Model Theory of Nowak and Wameryd Campaign, Persuasive Theory, Social Marketing Model and the choice of media involved in message spreading. The result of the research shows that to the working mothers who want to give exclusive breast milk to their babies are usually due to their knowledge about value and practices of breast feeding supported by husband, family, medical personnels, maternity clinics and their working places. But, the success of socialization on exclusive breast milk campaign is highly important based on the willingness of the mother to breast feed and give exclusive breast milk because mothers realize how high the value and the practices of breast feeding are.